Mobile Website User Experience (UX) Evaluation on Indonesia's Online Marketplace - Pratama, Khosyi Yoga; Purnama, James; Ipung, Heru Purnomo (Journal of Applied Information, Communication and Technology, 2016)
Internet economy is growing in Indonesia, and so is the smartphone usage. The popularity of online marketplace is getting bigger by the day yet the market is not utilized as best as it could. A lot of new smartphone user may not be familiar with the concept of mobile application, yet they browse for products to purchase using their mobile web browser. Therefore a mobile website User Experience (UX) evaluation on online marketplace in Indonesia is needed. By using User Experience Questionnaire (UEQ), this research hopes to evaluate which aspect of a marketplace’s mobile website is looked for by its users. An interview is conducted to 30 people to simulate shopping experience on Tokopedia and Bukalapak using a mobile web browser. The result shows that users prefers shopping without having to register, thus making online shopping quick and easy. In addition, user prefers to have all information they need regarding a product in one page rather than having to perform many action to reveal more information.